Air pollution in central Sweden. Deposition and effects October 1992 - September 1993; Luftfoeroreningar i mellersta Sverige; Nedfall och effekter oktober 1992 - september 1993 - "Hallgren Larsson, E"; "Westling, O" (1994)
The purpose of the monitoring programme is to quantify sulphur and nitrogen deposition to forests, and to illustrate possible acidification of the soil. Deposition is investigated by precipitation studies in open field areas and by throughfall studies in forest stands. Soil-water chemistry is examined in the forest stands and used as indication of soil condition. This report concerns the hydrological year from October 1992 through September 1993 for 38 locations in six counties in central Sweden. Precipitation pH-values averaged 4.5 to 4.6. All areas showed higher deposition of sulphur in forest stands than the critial load, 2.5-3.0 kg per hectare and year. The highest amounts were found at cape Vaermlandsnaes in lake Vaenern, Gladoe outside Huddinge in the county of Stockholm, and the forest stand outside Norrkoeping in the county of Oestergoetland. Sulphur deposition at the rest of the locations amounted 3.4 to 8.9 kg per hectare. Wet deposition of nitrogen amounted between 2.6 and 8.5 kg per hectare. Most throughfall samples showed lower values. Results from the county of Stockholm showed higher values of nitrogen deposition than open field measurements at three out of eight locations. The critial load of nitrogen for this region is 4-5 kg per heactare and year. With the exception for the northwestern parts, only wet deposition showed higher values at most locations. With a few exceptions, nitrogen in soilwater showed low values depending on biosorption of nitrogen in the ecosystem. Low soilwater pH ({approx}4.5) have mainly been found in the county of Oerebro. Together with small amounts of base cations and large amounts of aluminium this indicated that soil acidification was more advanced in this area, compared to the other areas. High pH-values, indicating satisfying buffering capacity, have mainly been found in soilwater from one forest stand in the norhern part of the county of Stockholm and three areas in the county of Soedermanland.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "SWEDEN"; "AIR POLLUTION MONITORING"; "SOILS"; "ACIDIFICATION"; "DEPOSITION"; "THROUGHFALL"; "AIR POLLUTION"; "PH VALUE"; "WATER CHEMISTRY"; "METEORIC WATER"; "CANOPIES"; "FORESTS"; "SPRUCES"; "SULFATES"; "NITRATES"; "HYDROGEN IONS"; "SULFUR"; "NITROGEN"; "CALCIUM"; "MAGNESIUM"; "POTASSIUM"; "COMPILED DATA"; "540120"; "CHEMICALS MONITORING AND TRANSPORT"